2020
DOI: 10.1158/0008-5472.can-19-3971
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the MYC-Regulated Glutaminase Metabolic Axis Is an Effective Synthetic Lethal Approach for Treating Chemoresistant Ovarian Cancers

Abstract: Amplification and overexpression of the MYC oncogene in tumor cells, including ovarian cancer cells, correlates with poor responses to chemotherapy. As MYC is not directly targetable, we have analyzed molecular pathways downstream of MYC to identify potential therapeutic targets. Here we report that ovarian cancer cells overexpressing glutaminase (GLS), a target of MYC and a key enzyme in glutaminolysis, are intrinsically resistant to platinum-based chemotherapy and are enriched with intracellular antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 43 publications
2
48
0
Order By: Relevance
“…Lee et al reported a successful inhibition of undifferentiated pleomorphic sarcoma (UPS) tumor growth with CB-839 (135). Combination therapy of CB-839 and PARP inhibitor olaparib also showed prolonged survival in a xenograft model of ovarian cancer (136). However, Biancur et al found no antitumor effect of CB-839 in both autochthonous and subcutaneous mouse models of PDAC (130).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Lee et al reported a successful inhibition of undifferentiated pleomorphic sarcoma (UPS) tumor growth with CB-839 (135). Combination therapy of CB-839 and PARP inhibitor olaparib also showed prolonged survival in a xenograft model of ovarian cancer (136). However, Biancur et al found no antitumor effect of CB-839 in both autochthonous and subcutaneous mouse models of PDAC (130).…”
Section: Glutaminase Inhibitor Based Therapeutic Strategymentioning
confidence: 99%
“…Therefore, Gln deprivation may cause increased ROS due to GSH suppression [ 66 , 74 ]. Indeed, reducing cellular Gln levels during Gln withdrawal [ 75 ], GLS knockdown, or exposure of cells to the GLS inhibitor CB-839 all resulted in a robust induction of ROS in high GLS-expressing but not in low GLS-expressing ovarian cancer cells [ 76 ], further supporting the roles of GLS in ROS production…”
Section: Common Mechanisms Associated With Pro- Gln- Asn- and Arg-mentioning
confidence: 99%
“…Dual inhibition of PARP (Olaparib) and CDK4/6 (Palbociclib) inhibits the growth of ovarian cancer cells in vitro and slows down tumor growth in vivo in part by inducing homologous recombination (HR) deficiency in a MYC-dependent manner (92). Concomitant upregulation of glutaminase (GLS) and c-MYC has been observed in platinum-resistant ovarian cancer cells (93). Inhibition of GLS-a downstream target of c-MYCby CB-839 sensitizes ovarian cancer cells to PARP inhibition and prolong survival in tumor-bearing mice (93).…”
Section: Small-molecule Inhibitorsmentioning
confidence: 99%